OPTIMIZATION OF INJECTION MOLDING PARAMETERS: IMPROVING MECHANICAL PROPERTIES OF KENAF REINFORCED POLYPROPYLENE COMPOSITES - Md Radzi, M.K.F.; Muhamad, N.; Sulong, A.B.; Haron, C.H.C.; Razak, Z.; Akhtar, M.N.; Ismail, N.F.; Tholibon, D.; Tharazi, I. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Natural fiber composites offer significant benefits as alternative material composites in terms of renewable materials. Therefore, natural fibers are commonly used in automotive industries primarily as interior and exterior parts. The manufacturing process of the automotive parts is essential to minimize the defects such as residual stress with better mechanical properties. Hence, this study focused on the employment of rational design of experiment (DOE) to determine the optimized injection molding parameters by improving the mechanical properties of kenaf fibers reinforced polypropylene composites. Taguchi method with L27 (34)orthogonal array applied to optimize the injection molding process parameters, based on the highest response of the strength properties generated by S/N ratio using the larger the better. Moreover, ANOVA analysis was employed to evaluate the most significant parameter including injection temperature, injection pressure, holding pressure and injection rate which affected the mechanical properties. The confirmation test was conducted to verify the predicted range of optimum mechanical properties. Results indicated that the optimum injection molding parameter obtained with the injection temperature at 190 °C, injection pressure at 1300 bar, holding pressure at 1900 bar, and the injection rate at 20 cm³/s. Implementing the optimum parameters is able to fabricate better mechanical properties of kenaf/PP composites where most of the confirmation mechanical strength values are evaluated within the predicted range or lie near the acceptable limits.